THE DEVELOPMENT OF ASSESSMENT INSTRUMENT FOR SPIRITUAL CHARACTER IN KINDERGARTEN - Umi Faizah; Setyoadi Purwanto (Sunan Kalijaga International Journal on Islamic Educational Research, 2021)
The aim of study is the development of a valid and reliable spiritual instrument to assess the achievements of early childhood spiritual characters in kindergarten/islamic kindergarten. This study using the quantitative and qualitative approaches. The determination of the construct of the spiritual aspect appraisal instrument is done through the opinion of character education experts, measurement experts, TK / RA / PAUD experts and Islamic education experts. From the assessment of 7 experts is then analyzed using Aiken's formula. Which assesses the validity of the contents of the instrument. the subjects of this study were group B in RA DPW UIN Sunan Kalijaga, RA Nurul Dzikri, TK Islam Tunas Melati, and TK Plus Salsabila Pandowo Harjo Sleman Yogyakarta. The reliability of this character assessment instrument was analyzed using cronbach’s alpha. The data collection was using a questionnaire, documentation, interview, observation, as well as Focus Group Discussion (FGD). The results of this study are as follows. (1) Based on the analysis of Formula Aiken's Vasi, the overall result of the indicator has an aiken index of 0.714 to 1,000, when taken on average by 0, 901; (2) The reliability of the developed instrument is quite good, seen from the Cronbach Alpha research is 0.914.